2021
DOI: 10.1177/0300985820988145
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Tumors and Histiocytomas in Domestic Goats and Diagnostic Utility of CD117/c-Kit and Iba1 Immunohistochemistry

Abstract: Cutaneous round cell tumors in goats present a diagnostic challenge. In this article, we provide a description of caprine cutaneous mast cell tumors (MCT) and histiocytomas, and report on the validation of anti-human antibodies to CD117/KIT and Iba1 by immunohistochemistry on a range of caprine tissues. Cells immunolabeled for CD117/KIT included resident mast cells in normal lung and skin, interstitial cells of Cajal (intestine), and neuronal cell bodies (brain). Cells immunolabeled for Iba1 included resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Many studies have shown that c-kit plays a very important role in the occurrence and development of different cancers 7 . The overexpression of c-kit can promote the occurrence and development of KIT-dependent cell types of tumors, such as gastrointestinal stromal tumors, mast cell tumors, and germ cell tumors 8 . For gastrointestinal stromal tumors, leukemias and other tumors with abnormally high expression of c-kit, drugs that downregulate the expression of c-kit have already been available and have good clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that c-kit plays a very important role in the occurrence and development of different cancers 7 . The overexpression of c-kit can promote the occurrence and development of KIT-dependent cell types of tumors, such as gastrointestinal stromal tumors, mast cell tumors, and germ cell tumors 8 . For gastrointestinal stromal tumors, leukemias and other tumors with abnormally high expression of c-kit, drugs that downregulate the expression of c-kit have already been available and have good clinical effects.…”
Section: Introductionmentioning
confidence: 99%